Digital entrepreneurship literacy model for rural youth entrepreneurs - Nizam Lani, Wahidah Hashim, Zaleha Mohamad, Muhammad Afiq Ahmad Khairuddin, Mohd (Opción, 2019)
This research models the relationship between passion, attitude, Internet usage and age in nurturing digital literacy and narrowing the knowledge gaps between urban and rural settings via statistical analysis as a method. As a result, more people in Malaysia are passionate about digital entrepreneurship, have a good attitude to becoming digital entrepreneurs and tend to use the Internet as their source medium. In conclusion, successful entrepreneurs need to be young, passionate, have a good attitude and be willing to spend hours studying the Internet.